Sandwich-structured metal-semiconductor-metal MSM photoelectric detector with avalanche effect and preparation method thereof

By adopting an avalanche-effect sandwich structure in UV photodetector, combining an oxidized diamond substrate and doped TiO2 layer, the problems of increased conductivity and low response speed are solved, and higher photodetector response speed and stability are achieved .

CN119170685APending Publication Date: 2024-12-20TAIYUAN UNIVERSITY OF TECHNOLOGY
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411329742.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The existing TiO2-based ultraviolet photodetectors have increased conductivity under high temperature or strong light, dark current increases, low response speed and sensitivity, and the nanotube structure has low durability in the external environment, affecting device performance.

Method used

Metal-semiconductor-metal MSM photodetectors with an avalanche effect sandwich structure, including diamond substrate layer, TiO2 layer, interdigital electrode layer and metal-doped TiO2 layer with an avalanche effect, to use diamond to derive heat, Mg, Yb or Ta doping increases the bandwidth of the band gap, and the Al2O3 package layer improves stability, forming a sandwich structure to improve response speed and sensitivity.

Benefits of technology

Through the combination of diamond substrate and doped TiO2 layer, the response speed and sensitivity of the photodetector are improved, dark current is reduced, the stability and durability of the device are enhanced, and the increase in conductivity and response speed in the prior art are solved. Low problem.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119170685A_ABST
    Figure CN119170685A_ABST
Patent Text Reader

Abstract

The invention relates to a sandwich-structured metal-semiconductor-metal MSM photoelectric detector with an avalanche effect and a preparation method thereof, and belongs to the technical field of photoelectric detector manufacturing. The photoelectric detector comprises a diamond substrate layer, a TiO2 layer, an interdigital electrode layer, a metal-doped TiO2 layer and an Al2O3 packaging layer from bottom to top, and the preparation method comprises the following steps: putting diamond into a deposition system to oxidize the surface of the diamond, and further preparing the TiO2 layer on the diamond; taking out the sample, and covering the TiO2 layer with an interdigital mask to prepare an interdigital electrode layer; taking out the sample, shielding two sides of the interdigital electrode layer by using a shielding object, and continuously putting the interdigital electrode layer into a deposition system to prepare a metal-doped TiO2 layer; and finally, plating an Al2O3 packaging layer. The photoelectric detector is scientific in design, novel in structure and excellent in performance. The preparation method of the photoelectric detector has the advantages of being convenient to operate, good in controllability and repeatability, small in error and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of photoelectric detector manufacturing, in particular to a metal-semiconductor-metal MSM photoelectric detector with a sandwich structure having an avalanche effect and a manufacturing method thereof. Background Art

[0002] Ultraviolet photodetectors use the photoelectric effect of semiconductor materials to convert light energy into electrical signals. They have been widely used in aerospace, environmental monitoring, medical and health fields. This requires that the film used in the photosensitive part of the ultraviolet photodetector has a large bandgap width, excellent chemical stability, high optical transparency, etc. 2 The film has a large bandgap (3.0-3.2 eV), good chemical stability and corrosion resistance, and a very small absorption coefficient for visible light, but exhibits strong absorption characteristics for ultraviolet light below 380 nm. It also has the advantages of low cost and simple preparation method, and shows broad application prospects in the preparation of ultraviolet photodetectors.

[0003] However, currently TiO 2 There are still some shortcomings of TiO-based UV detectors: on the one hand, 2 As a wide bandgap semiconductor, its intrinsic conductivity increases after high temperature or strong light exposure, resulting in more defect states being activated and dark current rising. On the other hand, TiO 2 The recombination rate of photogenerated electron-hole pairs in the TiO-based UV detector is high. 2 The mobility in the electron hole is low. After illumination, the internal heat causes the scattering rate of the carriers to increase and the mobility of the electron-hole pairs to decrease again, which ultimately leads to low response speed and sensitivity. There are two main solutions to the above problems: one is to use materials such as BiOCl or CuI and TiO 2 The heterojunction ultraviolet photodetector can achieve a wide spectrum response from ultraviolet to visible light, improve the separation efficiency of carriers, and thus improve the sensitivity and response speed of the detector; however, the defects and trap states at the heterojunction interface will affect the mobility and lifetime of carriers, reduce device performance, and some heterojunction materials may experience interface degradation or performance degradation during long-term operation. Another method is to use TiO with a high specific surface area. 2 Nanotubes increase the effective area of ​​light absorption and improve the generation efficiency of photogenerated electron-hole pairs. The structure of nanotubes provides an efficient electron transmission path, reduces the probability of carrier recombination, and improves the photoelectric conversion efficiency. At the same time, by controlling the size and structure of nanotubes, the TiO 2The band gap of the nanotubes can be reduced, thereby optimizing the photoelectric performance in the ultraviolet region. However, the interface bonding quality between the nanotubes and the electrode materials has a great influence on the device performance. Interface defects may lead to a decrease in carrier transfer efficiency. In addition, the nanotube structure shows low strength and durability in the external environment, which affects the service life of the device. Summary of the invention

[0004] The purpose of the present invention is to solve the problems existing in the above-mentioned prior art and to provide a sandwich structured metal-semiconductor-metal MSM photoelectric detector with an avalanche effect.

[0005] The present invention is achieved through the following technical solutions: A metal-semiconductor-metal MSM photodetector with a sandwich structure having an avalanche effect, comprising a diamond substrate layer with an oxidized surface, and TiO deposited on the diamond substrate layer 2 layer, TiO 2 A cross-finger electrode layer is deposited on the layer, and a metal-doped TiO 2 layer, metal-doped TiO 2 Al is deposited on the layer 2 O 3 Encapsulation layer; Diamond substrate layer and TiO 2 The length and width of the layer are the same, and the two are aligned vertically; metal-doped TiO 2 Layer and Al 2 O 3 The length and width of the encapsulation layer are the same, and the two are aligned up and down; the metal-doped TiO 2 Layer and Al 2 O 3 The length and width of the encapsulation layer are smaller than those of the diamond substrate layer and TiO 2 Layer length, width, metal-doped TiO 2 Layer and Al 2 O 3 The encapsulation layer is located between the diamond substrate layer and the TiO 2 At the center of the layer, both sides of the interdigitated electrode layer are exposed to the metal-doped TiO 2 Layer on both sides outside.

[0006] As a preferred technical solution, TiO 2 The thickness of the layer is 200~300 nm, the thickness of the interdigital electrode layer is 40~50 nm, and the metal-doped TiO 2 The thickness of the layer is 200~300 nm, Al 2 O 3 The thickness of the encapsulation layer is 10~20 nm.

[0007] The photodetector of the present invention uses diamond as a substrate to quickly remove the heat inside the photodetector and avoid the reduction of electron-hole pair mobility; TiO doped with Mg, Yb or Ta can be used to 2 To improve the metal-doped TiO 2 The bandgap width of the layer is reduced, and the intrinsic conductivity is reduced; Al with high UV transmittance is used 2 O 3 Encapsulation layer protects metal-doped TiO 2 The TiO layer is protected from the influence of the external environment, and the stability of the photodetector is improved while maintaining its good light transmittance. 2 layer, interdigitated electrode layer, metal-doped TiO 2 The layers form a sandwich structure, and the avalanche effect produced by the sandwich structure improves the response speed and sensitivity of the ultraviolet photodetector.

[0008] Furthermore, the present invention also provides a method for preparing the above-mentioned sandwich structure metal-semiconductor-metal MSM photoelectric detector with avalanche effect, comprising the following steps: A. Oxidation of diamond surface: Soak the diamond in acetone and distilled water and clean it with ultrasonic. 2 After drying, place in vacuum deposition system, roughly evacuate, and introduce O 2 Then, the diamond surface is oxidized to obtain a diamond substrate layer with an oxidized surface; B. Preparation of TiO 2 Layer: Close O 2 And turn on the molecular pump, when the vacuum degree is 10 -3 ~10 -4 When Ar and O were introduced into the vacuum deposition system, 2 , TiO is deposited on the surface of the diamond substrate 2 layer; C. Preparation of interdigital electrode layer: Take out the deposited sample, cover the sample surface with a mask, put the sample into the vacuum deposition system again, and 2 A metal film is plated on the layer, and the deposited sample is taken out, and the mask is removed to obtain the interdigital electrode layer; D. Preparation of Metal-doped TiO 2 Layer: Use shielding objects to cover both sides of the interdigital electrode layer, then put the sample into a vacuum deposition system to prepare metal-doped TiO on the interdigital electrode layer. 2 layer; E. Preparation of Al 2 O 3 Encapsulation layer: Metal-doped TiO 2 Al layer surface deposition preparation 2 O 3 Encapsulation layer.

[0009] As a preferred technical solution, the vacuum deposition system adopts a sputtering system, a vacuum evaporation system or a pulsed laser deposition system.

[0010] As a preferred technical solution, in step A, the diamond is ultrasonically cleaned with acetone and distilled water for 15 to 20 minutes, using N 2 The temperature is 80~100 ℃; when the vacuum deposition system adopts a sputtering system, the surface oxidation conditions are: vacuum degree is 2~3 Pa, O 2 The flow rate is 40~120 sccm, the bias power is 40~50 W, the substrate temperature is 500~600 ℃, and the oxidation time is 2~3 h. When the vacuum deposition system adopts a vacuum evaporation system, the surface oxidation conditions are: vacuum degree is 2~3Pa, O 2 The flow rate is 40~120 sccm, the current is 120~140 A, and the oxidation time is 5~6 h. When the vacuum deposition system adopts a pulsed laser deposition system, the surface oxidation conditions are: vacuum degree is 2~3 Pa, O 2 The flow rate was 40~120 sccm, the incident laser energy was adjusted to 400~500 mJ, the frequency was 5~6 Hz, and the oxidation time was 4~6 h.

[0011] As a preferred technical solution, in step B, when the vacuum deposition system adopts a sputtering system, the Ar flow rate is 50-80 sccm, O 2 The flow rate is 30~50 sccm, the Ti target power is 100~200 W, and the deposition time is 20~30 min; when the vacuum deposition system adopts a vacuum evaporation system, the Ar flow rate is 50~80 sccm, O 2 The flow rate is 30~50 sccm, the current is 95~100 A, and the deposition time is 50~60 min. When the vacuum deposition system adopts a pulsed laser deposition system, the Ar flow rate is 50~80 sccm, O 2 The flow rate is 30~50 sccm, the incident laser energy is 200~300 mJ, the frequency is 5~6 Hz, and the deposition time is 80~100 min. Finally, the TiO 2 The thickness of the layer is 200~300 nm.

[0012] As a preferred technical solution, in step C, when the vacuum deposition system adopts a sputtering system, the mask deposition parameters are: 30-60 sccm Ar is introduced, the metal target power is set to 50-100 W, and the deposition time is 4-5 min; when the vacuum deposition system adopts a vacuum evaporation system, the mask deposition parameters are: 30-60 sccm Ar is introduced, the current is adjusted to 150-200 A, and the deposition time is 5-10 min; when the vacuum deposition system adopts a pulsed laser deposition system, the mask deposition parameters are: 30-60 sccm Ar is introduced, the incident laser energy is adjusted to 500-600 mJ, the frequency is 5-6 Hz, and the deposition time is 20-30 min; when the metal film is plated, the material of the mask is quartz, silicon or copper, and the metal is a high work function metal, and the high work function metal includes Au, Pt, Ni, W and Ag; in the obtained interdigitated electrode layer, the interdigit length is 1.4-2 mm, and the interdigit spacing is 100-150 μm, and the interdigital width is 100~150 μm; finally, the thickness of the interdigital electrode layer is 40~50 nm.

[0013] As a preferred technical solution, in step D, when the shielding object shields both sides of the interdigitated electrode layer, the length of the shielding part is 300-700 μm and the width is 200-500 μm; during deposition and doping, the target materials used include the following three types: the first type is an independent Ti target and an independent doped metal target, the second type is an alloy target of doped metal and Ti, and the third type is an embedded target in which a doped metal column is embedded in Ti, wherein the doped metal is Mg, Yb or Ta; during the deposition process, when the vacuum deposition system adopts a sputtering system, the system vacuum degree is 10 -3 ~10 -4 Pa, Ar flow rate is 40~80 sccm, O 2 The flow rate is 20~50 sccm, the target power is set to 30~150 W, and the deposition time is 20~40 min; when the vacuum deposition system adopts a vacuum evaporation system, the system vacuum degree is 10 -3 ~10 -4 Pa, Ar flow rate is 40~80 sccm, O 2 The flow rate is 20~50 sccm, the target current is set to 40~100 A, and the deposition time is 50~60 min; when the vacuum deposition system adopts a pulsed laser deposition system, the system vacuum degree is 10 -3 ~10 -4 Pa, Ar flow rate is 40~80 sccm, O 2 The flow rate was 20-50 sccm, the incident laser energy was adjusted to 150-500 mJ, the frequency was 5-6 Hz, and the deposition time was 60-80 min. Finally, the metal-doped TiO2 The thickness of the layer is 200~300nm.

[0014] As a preferred technical solution, in step E, after deposition in the vacuum deposition system, turn off the power supply related to the doped target and turn on the deposition Al 2 O 3 Power supply related to the encapsulation layer; during the deposition process, when the vacuum deposition system adopts a sputtering system, the system vacuum degree is 10 -3 ~10 -4 Pa, Ar flow rate is 40~80 sccm, O 2 The flow rate is 20~50 sccm, the Al target power is set to 30~50W, and the deposition time is 2~3 min; when the vacuum deposition system adopts a vacuum evaporation system, the system vacuum degree is 10 -3 ~10 -4 Pa, Ar flow rate is 40~80 sccm, O 2 The flow rate is 20~50 sccm, the current is adjusted to 50~60 A, and the sputtering time is 8~10 min; when the vacuum deposition system adopts a pulsed laser deposition system, the system vacuum degree is 10 -3 ~10 -4 Pa, Ar flow rate is 40~80 sccm, O 2 The flow rate was 20-50 sccm, the incident laser energy was adjusted to 200-300 mJ, the frequency was 5-6 Hz, and the deposition time was 6-8 min. Finally, the Al 2 O 3 The thickness of the encapsulation layer is 10~20 nm.

[0015] As a preferred technical solution, in the alloy target, the weight ratio of the doped metal is 1:4~1:5; in the mosaic target, the area ratio of the doped metal is 1:8~1:4.

[0016] The photoelectric detector of the present invention has scientific design, novel structure and excellent performance. The preparation method of the photoelectric detector of the present invention has the advantages of convenient operation, good controllability, good repeatability and small error. 2 After doping with high work function metals such as Mg, Yb or Ta, the change in the Ti-O bond length causes an increase in the band gap, making it easier to excite electron-hole pairs under high electric fields, while increasing the carrier concentration and making the avalanche effect more likely to occur. 2 Layer, metal-doped TiO 2 The layers form a sandwich structure, due to the TiO 2 Metal-doped TiO 2There are interface defects between them. The existence of defects destroys the periodic potential field generated by the strictly periodic arrangement of atoms, thereby forming energy levels that allow electrons to be introduced into the semiconductor band gap. These defect energy levels can freely exchange electrons with the conduction band and act as traps. The traps at the interface capture holes to produce photoconductivity gain.

[0017] Avalanche effect originates from Mg, Yb or Ta doped TiO 2 Impact ionization process inside the TiO layer: 2 and Mg, Yb or Ta doped TiO 2 The contact forms a channel, and when the applied electric field is large enough, the electric field accelerates the movement of carriers and generates electron-hole pairs in high-energy collisions with atoms or other carriers. These new carrier pairs further increase the current.

[0018] The thermal conductivity of diamond is about 900-2320 W / (m·K), which is much higher than other common materials in nature. Using diamond as a substrate can quickly remove the internal heat of the photodetector, avoid the increase of carrier concentration inside the material due to internal heat, and slow down the rate at which electrons or holes absorb heat energy from the excited state and return to the ground state, thereby improving the response speed and sensitivity of the detector. At the same time, the bandgap width of diamond is relatively large at 5.5 eV, which can reduce the current formed by the substrate absorbing visible light and reduce the dark current of the photodetector. After oxidizing the diamond surface, the chemical activity and hydrophilicity of the diamond surface are improved, the compatibility with other materials is enhanced, the adhesion of the thin film on the diamond substrate is improved, and the performance of electronic devices with diamond as the substrate is improved. Ultra-thin Al 2 O 3 As an encapsulation layer, the thin film can not only prevent the influence of external water vapor on the photodetector, but also reduce the dark current with its large bandgap width. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments of the present invention are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0020] Figure 1 Schematic diagram of various shapes of the interdigitated electrode layer in the present invention.

[0021] Figure 2 Schematic diagram of the preparation process of the photoelectric detector of the present invention.

[0022] Figure 3 It is a plan view schematic diagram of the photodetector of the present invention.

[0023] Figure 4 It is a cross-sectional schematic diagram of the photodetector of the present invention.

[0024] Figure 5 for Figure 4 Schematic diagram of the electron channel shown in part A.

[0025] In the figure: 1-diamond substrate layer, 2-TiO 2 layer, 3-interdigitated electrode layer, 4-metal-doped TiO 2 Layer, 5-Al 2 O 3 Encapsulation layer. DETAILED DESCRIPTION

[0026] The embodiments of the technical solution of the present invention will be described in detail below in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present invention, and are therefore only used as examples, and the protection scope of the present invention cannot be limited thereto. It should be noted that, unless otherwise specified, the technical terms or scientific terms used in this application should be the common meanings understood by those skilled in the art to which the present invention belongs.

[0027] In the description of the present invention, it is necessary to understand that the orientations or positional relationships indicated by the terms "upper", "lower", "center", "both sides", etc. are based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present invention.

[0028] The present invention provides a sandwich structure metal-semiconductor-metal MSM photoelectric detector with avalanche effect, such as Figure 3 and Figure 4 As shown, the diamond substrate layer 1 includes a surface oxidized diamond substrate layer 1, on which TiO is deposited. 2 Layer 2, TiO 2 The interdigital electrode layer 3 is deposited on the layer 2, and the metal-doped TiO 2 Layer 4, metal-doped TiO 2 Al is deposited on layer 4 2 O 3 Encapsulation layer 5; Diamond substrate layer 1 and TiO 2 The length and width of layer 2 are the same, and the two are aligned vertically; the metal-doped TiO 2 Layer 4 and Al 2 O 3 The length and width of the encapsulation layer 5 are the same, and the two are aligned vertically; the metal-doped TiO 2 Layer 4 and Al 2 O 3The length and width of the encapsulation layer 5 are smaller than those of the diamond substrate layer 1 and the TiO 2 The length and width of layer 2, metal-doped TiO 2 Layer 4 and Al 2 O 3 The encapsulation layer 5 is located entirely between the diamond substrate layer 1 and the TiO 2 At the center of the layer 2, both sides of the interdigitated electrode layer 3 are exposed to the metal-doped TiO 2 Layer 4 outside on both sides.

[0029] The preparation method of the sandwich structure metal-semiconductor-metal MSM photoelectric detector with avalanche effect is as follows: Figure 2 As shown, the following steps are included: A. Oxidation of diamond surface: Soak the diamond in acetone and distilled water and clean it with ultrasonic. 2 After drying, place in vacuum deposition system, roughly evacuate, and introduce O 2 The diamond surface is then oxidized to obtain a diamond substrate layer 1 with an oxidized surface.

[0030] In the specific implementation, the diamond is ultrasonically cleaned with acetone and distilled water for 15 to 20 minutes (15 minutes, 18 minutes, and 20 minutes in the preferred embodiment), and N 2 The temperature is 80-100°C (preferred embodiment 100°C, 80°C, 90°C); when the vacuum deposition system adopts a sputtering system, the surface oxidation conditions are: the vacuum degree is 2-3 Pa (preferred embodiment 2Pa, 3 Pa), O 2 The flow rate is 40-120 sccm (preferred embodiment 80 sccm, 40 sccm, 120 sccm), the bias power is 40-50 W (preferred embodiment 40 W, 45 W, 50 W), the substrate temperature is 500-600 ° C (preferred embodiment 500 ° C, 550 ° C, 600 ° C), and the oxidation time is 2-3 h (preferred embodiment 2 h, 3 h); when the vacuum deposition system adopts a vacuum evaporation system, the surface oxidation conditions are: the vacuum degree is 2-3 Pa (preferred embodiment 2 Pa, 3 Pa), O 2 The flow rate is 40-120 sccm (preferred embodiment 80 sccm, 40 sccm, 120 sccm), the current is 120-140 A (preferred embodiment 120 A, 130 A, 140 A), and the oxidation time is 5-6 h (preferred embodiment 5 h, 6 h); when the vacuum deposition system adopts a pulsed laser deposition system, the surface oxidation conditions are: the vacuum degree is 2-3 Pa (preferred embodiment 2 Pa, 3 Pa), O 2The flow rate is 40~120 sccm (preferred embodiment 80 sccm, 40 sccm, 120 sccm), the incident laser energy is adjusted to 400~500 mJ (preferred embodiment 400 mJ, 500 mJ), the frequency is 5~6 Hz (preferred embodiment 5 Hz, 6 Hz), and the oxidation time is 4~6 h (preferred embodiment 4 h, 5 h, 6 h).

[0031] B. Preparation of TiO 2 Layer 2: Close O 2 And turn on the molecular pump, when the vacuum degree is 10 -3 ~10 -4 When Ar and O were introduced into the vacuum deposition system, 2 , TiO is deposited on the surface of the diamond substrate layer 1 2 Layer 2.

[0032] In a specific implementation, when the vacuum deposition system adopts a sputtering system, the Ar flow rate is 50-80 sccm (preferably 50 sccm, 65 sccm, 80 sccm), 2 The flow rate is 30-50 sccm (preferred embodiment 30 sccm, 40 sccm, 50 sccm), the Ti target power supply is 100-200 W (preferred embodiment 100 W, 150 W, 200 W), and the deposition time is 20-30 min (preferred embodiment 20 min, 25 min, 30 min); when the vacuum deposition system adopts a vacuum evaporation system, the Ar flow rate is 50-80 sccm (preferred embodiment 50 sccm, 65 sccm, 80 sccm), O 2 The flow rate is 30-50 sccm (preferred embodiment 30 sccm, 40 sccm, 50 sccm), the current is 95-100 A (preferred embodiment 95-100 A, 95-100 A, 95-100 A), and the deposition time is 50-60 min (preferred embodiment 50 min, 55 min, 60 min); when the vacuum deposition system adopts a pulsed laser deposition system, the Ar flow rate is 50-80 sccm (preferred embodiment 50 sccm, 65 sccm, 80 sccm), O 2 The flow rate is 30-50 sccm (preferred embodiment 30 sccm, 40 sccm, 50 sccm), the incident laser energy is 200-300 mJ (preferred embodiment 200 mJ, 250 mJ, 300 mJ), the frequency is 5-6 Hz (preferred embodiment 5 Hz, 6 Hz), and the deposition time is 80-100 min (preferred embodiment 80 min, 90 min, 100 min); finally, the obtained TiO2 The thickness of layer 2 is 200-300 nm (TiO with thicknesses of 200 nm, 250 nm, 300 nm, etc. can be obtained). 2 Layer 2).

[0033] C. Preparation of interdigital electrode layer 3: Take out the deposited sample, cover the sample surface with a mask, put the sample into the vacuum deposition system again, and 2 A metal film is plated on the layer 2, and the deposited sample is taken out, and the mask is removed to obtain the interdigital electrode layer 3; wherein the interdigital electrode layer 3 has various shapes such as Figure 1 shown.

[0034] In specific implementation, when the vacuum deposition system adopts a sputtering system, the mask deposition parameters are: 30-60 sccm (preferred embodiment 30 sccm, 45 sccm, 60 sccm) Ar is introduced, the metal target power supply is set to 50-100 W (preferred embodiment 50 W, 75 W, 100 W), and the deposition time is 4-5 min (preferred embodiment 4 min, 5 min); when the vacuum deposition system adopts a vacuum evaporation system, the mask deposition parameters are: 30-60 sccm (preferred embodiment 30 sccm, 45 sccm, 60 sccm) Ar is introduced, the current is adjusted to 150-200 A (preferred embodiment 150 A, 175 A, 200 A), and the deposition time is 5-10 min (preferred embodiment 5 min, 8 min, 10 min); when the vacuum deposition system adopts a pulsed laser deposition system, the mask deposition parameters are: 30-60 sccm (preferred embodiment 30 sccm, 45 sccm, 60 sccm) Ar, adjust the incident laser energy to 500-600mJ (preferred embodiment 500 mJ, 350 mJ, 600 mJ), the frequency to 5-6 Hz (preferred embodiment 5 Hz, 6 Hz), and the deposition time to 20-30 min (preferred embodiment 20 min, 30 min); when plating the metal film, the material of the mask is quartz, silicon or copper, and the pattern of the mask is as follows Figure 1As shown; the metal uses a high work function metal, and the high work function metal includes Au, Pt, Ni, W and Ag; in the obtained interdigitated electrode layer 3, the interdigitated length is 1.4~2 mm (preferred embodiment 1.4 mm, 1.7 mm, 2 mm), the interdigitated spacing is 100~150 μm (preferred embodiment 100 μm, 135 μm, 150 μm), and the interdigitated width is 100~150 μm (preferred embodiment 100 μm, 135 μm, 150 μm); finally, the thickness of the obtained interdigitated electrode layer 3 is 40~50 nm (interdigitated electrode layers 3 with thicknesses of 40nm, 45 nm, 50 nm, etc. can be obtained).

[0035] D. Preparation of Metal-doped TiO 2 Layer 4: Use shielding objects to cover both sides of the interdigital electrode layer 3, and then put the sample into a vacuum deposition system to prepare metal-doped TiO on the interdigital electrode layer 3. 2 Layer 4.

[0036] In specific implementation, when the shielding object shields both sides of the interdigitated electrode layer 3, the length of the shielding part is 300-700 μm (preferred embodiment 300 μm, 500 μm, 700 μm), and the width is 200-500 μm (preferred embodiment 200 μm, 250 μm, 500 μm); during deposition and doping, the target materials used include the following three types: the first type is an independent Ti target and an independent doped metal target, the second type is an alloy target of doped metal and Ti, and the third type is an inlaid target in which a doped metal column is embedded in Ti, wherein the doped metal is Mg, Yb or Ta, the weight ratio of the doped metal in the alloy target is 1:4-1:5 (preferred embodiment 1:4, 1:5), and the area ratio of the doped metal in the inlaid target is 1:8-1:4 (preferred embodiment 1:4, 1:6, 1:8); during the deposition process, when the vacuum deposition system adopts a sputtering system, the system vacuum degree is 10 -3 ~10 -4 Pa (Preferred Embodiment 10 -3 Pa, 10 -4 Pa), Ar flow rate is 40-80 sccm (preferred embodiment 40 sccm, 60 sccm, 80 sccm), O 2 The flow rate is 20-50 sccm (preferred embodiment 20 sccm, 35 sccm, 50 sccm), the target power is set to 30-150 W (preferred embodiment 30 W, 90 W, 150 W), and the deposition time is 20-40 min (preferred embodiment 20 min, 30 min, 40 min); when the vacuum deposition system adopts a vacuum evaporation system, the system vacuum degree is 10 -3 ~10 -4 Pa (Preferred Embodiment 10-3 Pa, 10 -4 Pa), Ar flow rate is 40-80 sccm (preferred embodiment 40 sccm, 60 sccm, 80 sccm), O 2 The flow rate is 20-50 sccm (preferred embodiment 20 sccm, 35 sccm, 50 sccm), the target current is set to 40-100 A (preferred embodiment 40 A, 70 A, 100 A), and the deposition time is 50-60 min (preferred embodiment 50 min, 55 min, 60 min); when the vacuum deposition system adopts a pulsed laser deposition system, the system vacuum degree is 10 -3 ~10 -4 Pa (Preferred Embodiment 10 -3 Pa, 10 -4 Pa), Ar flow rate is 40-80 sccm (preferred embodiments are 40 sccm, 60 sccm, 80 sccm), O 2 The flow rate is 20-50 sccm (preferred embodiment 20 sccm, 35 sccm, 50 sccm), the incident laser energy is adjusted to 150-500 mJ (preferred embodiment 150 mJ, 350 mJ, 500 mJ), the frequency is 5-6 Hz (preferred embodiment 5 Hz, 6 Hz), and the deposition time is 60-80 min (preferred embodiment 60 min, 70 min, 80 min); finally, the obtained metal-doped TiO 2 The thickness of layer 4 is 200-300 nm (metal-doped TiO with thicknesses of 200 nm, 250 nm, 300 nm, etc. can be obtained). 2 Layer 4).

[0037] E. Preparation of Al 2 O 3 Encapsulation layer 5: Metal-doped TiO 2 Layer 4 surface deposition preparation Al 2 O 3 Encapsulation layer 5.

[0038] In the specific implementation, after deposition in the vacuum deposition system, turn off the power supply related to the doped target and turn on the deposition Al 2 O 3 During the deposition process, when the vacuum deposition system uses a sputtering system, the system vacuum degree is 10 -3 ~10 -4 Pa (Preferred Embodiment 10 -3 Pa, 10 -4Pa), Ar flow rate is 40-80 sccm (preferred embodiment 40 sccm, 60 sccm, 80 sccm), O 2 The flow rate is 20-50 sccm (preferred embodiment 20 sccm, 35 sccm, 50 sccm), the Al target power is set to 30-50 W (preferred embodiment 30 W, 40 W, 50 W), and the deposition time is 2-3 min (preferred embodiment 2 min, 3 min); when the vacuum deposition system adopts a vacuum evaporation system, the system vacuum degree is 10 -3 ~10 -4 Pa (Preferred Embodiment 10 -3 Pa, 10 -4 Pa), Ar flow rate is 40-80 sccm (preferred embodiment 40 sccm, 60 sccm, 80 sccm), O 2 The flow rate is 20-50 sccm (preferred embodiment 20 sccm, 35 sccm, 50 sccm), the current is adjusted to 50-60 A (preferred embodiment 50 A, 60 A), and the sputtering time is 8-10 min (preferred embodiment 8 min, 9 min, 10 min); when the vacuum deposition system adopts a pulsed laser deposition system, the system vacuum degree is 10 -3 ~10 -4 Pa (Preferred Embodiment 10 -3 Pa, 10 -4 Pa), Ar flow rate is 40-80 sccm (preferred embodiment 40 sccm, 60 sccm, 80 sccm), O 2 The flow rate is 20-50 sccm (preferred embodiment 20 sccm, 35 sccm, 50 sccm), the incident laser energy is adjusted to 200-300 mJ (preferred embodiment 300 mJ, 200 mJ, 250 mJ), the frequency is 5-6 Hz (preferred embodiment 5 Hz, 6 Hz), and the deposition time is 6-8 min (preferred embodiment 6 min, 7 min, 8 min); finally, the Al 2 O 3 The thickness of the encapsulation layer 5 is 10-20 nm (Al2O3 layers with thicknesses of 10 nm, 15 nm, 20 nm, etc. can be obtained). 2 O 3 Encapsulation layer 5).

[0039] The photodetector of the present invention adopts TiO 2 Thin film / interdigitated electrode / Mg(Yb or Ta) doped TiO 2 The sandwich structure of the film consists of the same oxide (TiO 2) structure, the deposition process requires a single target material, less pollution, and simple preparation; at the same time, the electron channel impurities formed by the same oxide are less and the band gap is uniform. Secondly, after doping with Mg, the Ti-O bond length becomes shorter and the band gap increases. 2 Electron channels are formed between the layers, such as Figure 5 As shown, the impact ionization is enhanced, and the controllable adjustment of the band gap is achieved by adjusting the Mg content. Thirdly, by using surface oxidized diamond as the substrate, its surface oxide layer can reduce the number of surface defect states and trap states, reduce the accumulation of surface charge and leakage current, and improve the quantum efficiency and dark current characteristics of the photodetector. At the same time, the larger bandgap width reduces the current generated by the substrate absorbing visible light and reduces the dark current; its internal diamond phase has high thermal conductivity, which can efficiently conduct heat inside the photodetector and improve the response speed and sensitivity of the detector. Finally, Al 2 O 3 As an encapsulation layer, the thin film can prevent surface reactions and its larger bandgap width can reduce dark current.

[0040] Furthermore, the technical scheme of the photoelectric detector and the preparation method thereof of the present invention is further described below by listing several specific preparation method embodiments. Example 1

[0041] The method for preparing the sandwich structure metal-semiconductor-metal MSM photoelectric detector having the avalanche effect comprises the following steps: A. Oxidation of diamond surface: Soak the diamond in acetone and distilled water and clean it with ultrasonic. 2 After drying, place in vacuum deposition system, roughly evacuate, and introduce O 2 Then, the diamond surface is oxidized to obtain a diamond substrate layer 1 with an oxidized surface; Specifically, the diamond was ultrasonically cleaned with acetone and distilled water for 15 min, and N 2 The temperature is 80 °C; the vacuum deposition system uses a sputtering system. After the diamond is placed in the sputtering chamber, the vacuum degree is adjusted to 2 Pa and O is introduced. 2 The flow rate was 40 sccm, the bias power was turned on at 40 W, the substrate temperature was adjusted to 500 °C, and the oxidation time was 2 h.

[0042] B. Preparation of TiO 2 Layer 2: Close O 2 And turn on the molecular pump, when the vacuum degree is 10 -4 When Ar and O were introduced into the vacuum deposition system, 2 , TiO is deposited on the surface of the diamond substrate layer 1 2 Layer 2; Specifically: After the oxidation is stopped, when the vacuum degree is 10 -4 When the Ar flow rate in the sputtering chamber is 50 sccm, O 2 The flow rate was 30 sccm, the Ti target power was set to 100 W, and the sputtering deposition time was 20 min. Finally, the obtained TiO 2 The thickness of layer 2 is 200 nm.

[0043] C. Preparation of interdigital electrode layer 3: Take out the deposited sample, cover the sample surface with a mask, put the sample into the vacuum deposition system again, and 2 A metal film is plated on layer 2, and the deposited sample is taken out, and the mask is removed to obtain the interdigital electrode layer 3; Specifically: TiO 2 The diamond substrate layer 1 of layer 2 is covered with a quartz mask and placed in a sputtering chamber to plate the Au interdigital electrode layer 3. The quartz mask is used Figure 1 In the (1) shape, the obtained interdigital length is 1.4 mm, the interdigital spacing is 100 μm, and the interdigital width is 100 μm; 40 sccm Ar is introduced into the sputtering chamber, the Au target power is set to 50 W, and the deposition time is 4 min; finally, the thickness of the obtained interdigital electrode layer 3 is 40 nm.

[0044] D. Preparation of Metal-doped TiO 2 Layer 4: Use shielding objects to cover both sides of the interdigital electrode layer 3, and then put the sample into a vacuum deposition system to prepare metal-doped TiO on the interdigital electrode layer 3. 2 Layer 4; Specifically, the Au interdigital electrode layer 3 is placed in the sputtering chamber after being shielded by shielding objects. The shielding parts at the left and right ends are 500 μm long and 400 μm wide. The targets used are independent Ti targets and independent Mg targets. The system vacuum degree is 10 -4 Pa, Ar flow rate is 40 sccm, O 2 The flow rate was 20 sccm, the Ti target power was set to 80 W, the Mg target power was set to 30 W, and the deposition time was 20 min. Finally, the Mg-doped TiO 2 The thickness of the layer is 200 nm.

[0045] E. Preparation of Al 2 O 3 Encapsulation layer 5: Metal-doped TiO 2 Layer 4 surface deposition preparation Al 2 O 3 Encapsulation layer 5.

[0046] Specifically: turn off the power supply related to the doped target and turn on the Al deposition 2 O 3 The power supply of encapsulation layer 5 is related; during the deposition process, the system vacuum degree is 10 -4 Pa, Ar flow rate is 40~80 sccm, O 2 The flow rate was 20-50 sccm, the Al target power was set to 30 W, and the deposition time was 2 min. 2 O 3 The thickness of the encapsulation layer 5 is 10 nm. Example 2

[0047] The method for preparing the sandwich structure metal-semiconductor-metal MSM photoelectric detector having the avalanche effect comprises the following steps: A. Oxidation of diamond surface: Soak the diamond in acetone and distilled water and clean it with ultrasonic. 2 After drying, place in vacuum deposition system, roughly evacuate, and introduce O 2 Then, the diamond surface is oxidized to obtain a diamond substrate layer 1 with an oxidized surface; Specifically, the diamond was ultrasonically cleaned with acetone and distilled water for 17 min, and N 2 The temperature is 80 °C; the vacuum deposition system uses a vacuum evaporation system. After the diamond is placed in the vacuum evaporation chamber, the vacuum degree is adjusted to 3 Pa and O is introduced. 2 The flow rate was 70 sccm, the regulated current was 140 A, and the oxidation time was 6 h.

[0048] B. Preparation of TiO 2 Layer: Close O 2 And turn on the molecular pump, when the vacuum degree is 10 -4 When Ar and O were introduced into the vacuum deposition system, 2 , TiO is deposited on the surface of the diamond substrate layer 1 2 Layer 2; Specifically: After the oxidation is stopped, when the vacuum degree is 10 -4 When Pa, the Ar flow rate into the vacuum evaporation chamber is 80 sccm, O 2 The flow rate was 50 sccm, the current was adjusted to 100 A, and the evaporation time was 60 min. Finally, the TiO 2 The thickness of layer 2 is 300 nm.

[0049] C. Preparation of interdigital electrode layer 3: Take out the deposited sample, cover the sample surface with a mask, put the sample into the vacuum deposition system again, and 2A metal film is plated on layer 2, and the deposited sample is taken out, and the mask is removed to obtain the interdigital electrode layer 3; Specifically: TiO 2 The diamond substrate layer 1 of layer 2 is covered with a copper mask and placed in a vacuum evaporation chamber to plate the Ag interdigital electrode layer 3. The copper mask is used Figure 1 The (2) shape in the figure has a finger length of 2 mm, a finger spacing of 150 μm, and a finger width of 150 μm. 50 sccm Ar is introduced into the vacuum evaporation chamber, the current is adjusted to 160 A, and the vacuum evaporation time is 8 min. Finally, the thickness of the obtained finger electrode layer 3 is 45 nm.

[0050] D. Preparation of Metal-doped TiO 2 Layer 4: Use shielding objects to cover both sides of the interdigital electrode layer 3, and then put the sample into a vacuum deposition system to prepare metal-doped TiO on the interdigital electrode layer 3. 2 Layer 4; Specifically, the left and right ends of the Ag interdigital electrode layer 3 were covered with shielding materials and then placed in a vacuum evaporation chamber. The length of the shielding parts at the left and right ends was 300 μm and the width was 200 μm. The target material used was an alloy target of Yb and Ti, in which the weight ratio of Yb was 1:4. The Ar flow rate was 40 sccm and O 2 The flow rate was 20 sccm, the current of the Yb and Ti alloy target was set to 82 A, and the reaction time was 55 min. Finally, the Yb-doped TiO 2 The thickness of the layer is 255 nm.

[0051] E. Preparation of Al 2 O 3 Encapsulation layer 5: Metal-doped TiO 2 Layer 4 surface deposition preparation Al 2 O 3 Encapsulation layer 5.

[0052] Specifically: turn off the power supply related to the doped target and turn on the Al deposition 2 O 3 The power supply of encapsulation layer 5 is related; during the deposition process, the system vacuum degree is 10 -4 Pa, Ar flow rate is 40~80 sccm, O 2 The flow rate was 20-50 sccm, the current was adjusted to 60 A, and the vacuum evaporation time was 10 min. Finally, the Al 2 O 3 The thickness of the encapsulation layer 5 is 20 nm. Example 3

[0053] The method for preparing the sandwich structure metal-semiconductor-metal MSM photoelectric detector having the avalanche effect comprises the following steps: A. Oxidation of diamond surface: Soak the diamond in acetone and distilled water and clean it with ultrasonic. 2 After drying, place in vacuum deposition system, roughly evacuate, and introduce O 2 Then, the diamond surface is oxidized to obtain a diamond substrate layer 1 with an oxidized surface; Specifically, the diamond was ultrasonically cleaned with acetone and distilled water for 17 min, and N 2 The temperature is 90 °C; the vacuum deposition system uses a pulsed laser deposition system. After the diamond is placed in the pulsed laser deposition chamber, the vacuum degree is adjusted to 2Pa and O is introduced. 2 The flow rate was 110 sccm, the incident laser energy was adjusted to 500 mJ, the frequency was 5 Hz, and the oxidation time was 5 h.

[0054] B. Preparation of TiO 2 Layer 2: Close O 2 And turn on the molecular pump, when the vacuum degree is 10 -4 When Ar and O were introduced into the vacuum deposition system, 2 , TiO is deposited on the surface of the diamond substrate layer 1 2 Layer 2; Specifically: After the oxidation is stopped, when the vacuum degree is 10 -4 When the Ar flow rate was 80 sccm, O 2 The flow rate was 40 sccm, the incident laser energy was adjusted to 300 mJ, the frequency was 5 Hz, and the deposition time was 80 min. Finally, the TiO 2 The thickness of layer 2 is 230 nm.

[0055] C. Preparation of interdigital electrode layer 3: Take out the deposited sample, cover the sample surface with a mask, put the sample into the vacuum deposition system again, and 2 A metal film is plated on layer 2, and the deposited sample is taken out, and the mask is removed to obtain the interdigital electrode layer 3; Specifically: TiO 2 The diamond substrate layer 1 of layer 2 is covered with a silicon mask and placed in a pulsed laser deposition chamber to plate a Pt interdigital electrode layer 3; the silicon mask is used Figure 1The (4) shape in the figure has a finger length of 1.7 mm, a finger spacing of 120 μm, and a finger width of 100 μm. 35 sccm Ar is introduced into the pulsed laser deposition chamber, the incident laser energy is adjusted to 550 mJ, the frequency is 5 Hz, and the deposition time is 20 min. Finally, the thickness of the obtained finger electrode layer 3 is 40 nm.

[0056] D. Preparation of Metal-doped TiO 2 Layer 4: Use shielding objects to cover both sides of the interdigital electrode layer 3, and then put the sample into a vacuum deposition system to prepare metal-doped TiO on the interdigital electrode layer 3. 2 Layer 4; Specifically, the left and right ends of the Pt interdigital electrode layer 3 were shielded with shielding objects and then placed in a pulsed laser deposition chamber. The shielding parts at the left and right ends were 400 μm in length and 300 μm in width. The target material used was a mosaic target obtained by embedding Ta columns in a Ti target, in which the area ratio of Ta was 1:6. The Ar flow rate was 80 sccm, and O 2 The flow rate was 50 sccm, the incident laser energy of the embedded target was adjusted to 300 mJ, the frequency was 5 Hz, and the deposition time was 65 min. Finally, the Ta-doped TiO 2 The thickness of the layer is 270 nm.

[0057] E. Preparation of Al 2 O 3 Encapsulation layer 5: Metal-doped TiO 2 Layer 4 surface deposition preparation Al 2 O 3 Encapsulation layer 5.

[0058] Specifically: turn off the power supply related to the doped target and turn on the Al deposition 2 O 3 The power supply of encapsulation layer 5 is related; during the deposition process, the system vacuum degree is 10 -4 Pa, Ar flow rate is 40~80 sccm, O 2 The flow rate was 20-50 sccm, the incident laser energy was adjusted to 200 mJ, the frequency was 5 Hz, and the deposition time was 7 min. Finally, the Al 2 O 3 The thickness of the encapsulation layer 5 is 15 nm. Example 4

[0059] The method for preparing the sandwich structure metal-semiconductor-metal MSM photoelectric detector having the avalanche effect comprises the following steps: A. Oxidation of diamond surface: Soak the diamond in acetone and distilled water and clean it with ultrasonic. 2After drying, place in vacuum deposition system, roughly evacuate, and introduce O 2 Then, the diamond surface is oxidized to obtain a diamond substrate layer 1 with an oxidized surface; Specifically, the diamond was ultrasonically cleaned with acetone and distilled water for 15 min, and N 2 The temperature is 80 °C; the vacuum deposition system uses a sputtering system. After the diamond is placed in the sputtering chamber, the vacuum degree is adjusted to 3 Pa and O is introduced. 2 The flow rate was 60 sccm, the bias power was turned on at 45 W, the substrate temperature was adjusted to 550 °C, and the oxidation time was 2 h.

[0060] B. Preparation of TiO 2 Layer 2: Close O 2 And turn on the molecular pump, when the vacuum degree is 10 -4 When Ar and O were introduced into the vacuum deposition system, 2 , TiO is deposited on the surface of the diamond substrate layer 1 2 Layer 2; Specifically: After the oxidation is stopped, when the vacuum degree is 10 -4 When the Ar flow rate in the sputtering chamber is 60 sccm, O 2 The flow rate was 50 sccm, the Ti target power was set to 200 W, and the sputtering deposition time was 20 min. Finally, the obtained TiO 2 The thickness of layer 2 is 300 nm.

[0061] C. Preparation of interdigital electrode layer 3: Take out the deposited sample, cover the sample surface with a mask, put the sample into the vacuum deposition system again, and 2 A metal film is plated on layer 2, and the deposited sample is taken out, and the mask is removed to obtain the interdigital electrode layer 3; Specifically: TiO 2 The diamond substrate layer 1 of layer 2 is covered with a quartz mask and placed in a vacuum evaporation chamber of a vacuum evaporation system to plate a Ni interdigital electrode layer 3. The quartz mask is used Figure 1 The (5th) shape in the figure has a finger length of 1.7 mm, a finger spacing of 130 μm, and a finger width of 120 μm. 50 sccmAr is introduced into the vacuum evaporation chamber, the current is adjusted to 170 A, and the vacuum evaporation time is 9 min. Finally, the thickness of the obtained finger electrode layer 3 is 48 nm.

[0062] D. Preparation of Metal-doped TiO 2 Layer 4: Use shielding objects to cover both sides of the interdigital electrode layer 3, and then put the sample into a vacuum deposition system to prepare metal-doped TiO on the interdigital electrode layer 3.2 Layer 4; Specifically, the left and right ends of the Ni interdigital electrode layer 3 were shielded with shielding objects and then placed in a pulsed laser deposition chamber in a pulsed laser deposition system. The shielding parts at the left and right ends were 600 μm in length and 400 μm in width. The target material used was a mosaic target obtained by embedding Mg columns in a Ti target, in which the area ratio of Mg was 1:5. The Ar flow rate was 40 sccm, and the O 2 The flow rate was 20 sccm, the incident laser energy of the embedded target was adjusted to 400 mJ, the frequency was 5 Hz, and the deposition time was 75 min. Finally, the Mg-doped TiO 2 The thickness of the layer is 300 nm.

[0063] E. Preparation of Al 2 O 3 Encapsulation layer 5: Metal-doped TiO 2 Layer 4 surface deposition preparation Al 2 O 3 Encapsulation layer 5.

[0064] Specifically: turn off the power supply related to the doped target and turn on the Al deposition 2 O 3 The power supply of encapsulation layer 5 is related; during the deposition process, the system vacuum degree is 10 -4 Pa, Ar flow rate is 40~80 sccm, O 2 The flow rate was 20-50 sccm, the incident laser energy was adjusted to 300 mJ, the frequency was 5 Hz, and the deposition time was 6 min. Finally, the Al 2 O 3 The thickness of the encapsulation layer 5 is 17 nm.

[0065] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some or all of the technical features may be replaced by equivalents. These modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present invention, and they should all be included in the scope of the claims and specification of the present invention.

Claims

1. A sandwich structured metal-semiconductor-metal MSM photodetector with an avalanche effect, characterized in that: It comprises a diamond substrate layer with an oxidized surface, a TiO2 layer deposited on the diamond substrate layer, an interdigital electrode layer deposited on the TiO2 layer, a metal-doped TiO2 layer deposited on the interdigital electrode layer, and an Al2O3 encapsulation layer deposited on the metal-doped TiO2 layer; the length and width of the diamond substrate layer and the TiO2 layer are the same, and the two are aligned vertically; the length and width of the metal-doped TiO2 layer and the Al2O3 encapsulation layer are the same, and the two are aligned vertically; the length and width of the metal-doped TiO2 layer and the Al2O3 encapsulation layer are both smaller than the length and width of the diamond substrate layer and the TiO2 layer, the metal-doped TiO2 layer and the Al2O3 encapsulation layer are located at the center of the diamond substrate layer and the TiO2 layer as a whole, and the left and right sides of the interdigital electrode layer are exposed outside the two sides of the metal-doped TiO2 layer.

2. The metal-semiconductor-metal MSM photoelectric detector with a sandwich structure and avalanche effect according to claim 1, characterized in that: The thickness of the TiO2 layer is 200~300 nm, the thickness of the interdigitated electrode layer is 40~50 nm, the thickness of the metal-doped TiO2 layer is 200~300 nm, and the thickness of the Al2O3 encapsulation layer is 10~20 nm.

3. The method for preparing the sandwich structure metal-semiconductor-metal MSM photoelectric detector with avalanche effect as claimed in claim 1, characterized in that: The steps include: A. Oxidation of diamond surface: Soak the diamond in acetone and distilled water and clean it with ultrasonic cleaning, dry it with N2 and put it into a vacuum deposition system, roughly evacuate it, and then oxidize the diamond surface by introducing O2 to obtain a diamond substrate layer with oxidized surface; B. Preparation of TiO2 layer: Turn off O2 and turn on the molecular pump. When the vacuum degree is 10 -3 ~10 -4 When Pa, Ar and O2 are introduced into the vacuum deposition system to deposit a TiO2 layer on the surface of the diamond substrate layer; C. Preparation of interdigital electrode layer: take out the deposited sample, cover the sample surface with a mask, put the sample into the vacuum deposition system again, plate a metal film on the TiO2 layer, take out the deposited sample again, and remove the mask to obtain the interdigital electrode layer; D. Preparation of metal-doped TiO2 layer: shielding the two sides of the interdigital electrode layer with a shielding object, and then placing the sample into a vacuum deposition system to prepare a metal-doped TiO2 layer on the interdigital electrode layer; E. Preparation of Al2O3 encapsulation layer: Deposition and preparation of Al2O3 encapsulation layer on the surface of the metal-doped TiO2 layer.

4. The method for preparing the sandwich structure metal-semiconductor-metal MSM photoelectric detector with avalanche effect according to claim 3, characterized in that: The vacuum deposition system adopts a sputtering system, a vacuum evaporation system or a pulsed laser deposition system.

5. The method for preparing the sandwich structure metal-semiconductor-metal MSM photoelectric detector with avalanche effect according to claim 4, characterized in that: In step A, the diamond is ultrasonically cleaned with acetone and distilled water for 15 to 20 min, and the temperature of N2 is 80 to 100 °C. When the vacuum deposition system adopts a sputtering system, the surface oxidation conditions are as follows: vacuum degree is 2 to 3 Pa, O2 flow rate is 40 to 120 sccm, bias power is 40 to 50 W, substrate temperature is 500 to 600 °C, and oxidation time is 2 to 3 h. When the vacuum deposition system adopts a vacuum evaporation system, the surface oxidation conditions are as follows: vacuum degree is 2 to 3 Pa, O2 flow rate is 40 to 120 sccm, current is 120 to 140 A, and oxidation time is 5 to 6 h. When the vacuum deposition system adopts a pulsed laser deposition system, the surface oxidation conditions are as follows: vacuum degree is 2 to 3 Pa, O2 flow rate is 40 to 120 sccm, incident laser energy is adjusted to 400 to 500 mJ, frequency is 5 to 6 Hz, and oxidation time is 4 to 6 h.

6. The method for preparing the sandwich structure metal-semiconductor-metal MSM photoelectric detector with avalanche effect according to claim 4, characterized in that: In step B, when the vacuum deposition system adopts a sputtering system, the Ar flow rate is 50-80 sccm, the O2 flow rate is 30-50 sccm, the Ti target power is 100-200 W, and the deposition time is 20-30 min; when the vacuum deposition system adopts a vacuum evaporation system, the Ar flow rate is 50-80 sccm, the O2 flow rate is 30-50 sccm, the current is 95-100 A, and the deposition time is 50-60 min; when the vacuum deposition system adopts a pulsed laser deposition system, the Ar flow rate is 50-80 sccm, the O2 flow rate is 30-50 sccm, the incident laser energy is 200-300 mJ, the frequency is 5-6 Hz, and the deposition time is 80-100 min; finally, the thickness of the obtained TiO2 layer is 200-300 nm.

7. The method for preparing a sandwich structure metal-semiconductor-metal MSM photoelectric detector with avalanche effect according to claim 4, characterized in that: In step C, when the vacuum deposition system adopts a sputtering system, the mask deposition parameters are: 30-60 sccm Ar is introduced, the metal target power is set to 50-100 W, and the deposition time is 4-5 min; when the vacuum deposition system adopts a vacuum evaporation system, the mask deposition parameters are: 30-60 sccm Ar is introduced, the current is adjusted to 150-200 A, and the deposition time is 5-10 min; when the vacuum deposition system adopts a pulsed laser deposition system, the mask deposition parameters are: 30-60 sccm Ar is introduced, the incident laser energy is adjusted to 500-600 mJ, the frequency is 5-6 Hz, and the deposition time is 20-30 min; when the metal film is plated, the material of the mask is quartz, silicon or copper, and the metal is a high work function metal, and the high work function metal includes Au, Pt, Ni, W and Ag; in the obtained interdigitated electrode layer, the interdigit length is 1.4-2 mm, and the interdigit spacing is 100-150 μm, and the interdigital width is 100~150 μm; finally, the thickness of the interdigital electrode layer is 40~50 nm.

8. The method for preparing the sandwich structure metal-semiconductor-metal MSM photoelectric detector with avalanche effect according to claim 4, characterized in that: In step D, when the shielding object shields both sides of the interdigitated electrode layer, the length of the shielding part is 300-700 μm and the width is 200-500 μm. During deposition and doping, the target materials used include the following three types: the first type is an independent Ti target and an independent doped metal target, the second type is an alloy target of doped metal and Ti, and the third type is an embedded target in which a doped metal column is embedded in Ti, wherein the doped metal is Mg, Yb or Ta. During the deposition process, when the vacuum deposition system adopts a sputtering system, the system vacuum degree is 10 -3 ~10 -4 Pa, Ar flow rate is 40~80 sccm, O2 flow rate is 20~50 sccm, target power supply is set to 30~150 W, deposition time is 20~40 min; when the vacuum deposition system adopts vacuum evaporation system, the system vacuum degree is 10 -3 ~10 -4 Pa, Ar flow rate is 40~80 sccm, O2 flow rate is 20~50 sccm, target current is set to 40~100A, deposition time is 50~60 min; when the vacuum deposition system adopts pulse laser deposition system, the system vacuum degree is 10 -3 ~10 -4 Pa, Ar flow rate is 40~80 sccm, O2 flow rate is 20~50 sccm, the incident laser energy is adjusted to 150~500 mJ, the frequency is 5~6 Hz, and the deposition time is 60~80 min; finally, the thickness of the metal-doped TiO2 layer is 200~300 nm.

9. The method for preparing the sandwich structure metal-semiconductor-metal MSM photoelectric detector with avalanche effect according to claim 4, characterized in that: In step E, after deposition in the vacuum deposition system, the power supply related to the doped target is turned off, and the power supply related to the deposition of the Al2O3 encapsulation layer is turned on; During the deposition process, when the vacuum deposition system uses a sputtering system, the system vacuum degree is 10 -3 ~10 -4 Pa, Ar flow rate is 40~80 sccm, O2 flow rate is 20~50 sccm, Al target power is set to 30~50 W, and deposition time is 2~3 min; when the vacuum deposition system adopts a vacuum evaporation system, the system vacuum degree is 10 -3 ~10 -4 Pa, Ar flow rate is 40~80 sccm, O2 flow rate is 20~50 sccm, the adjustment current is 50~60 A, and the sputtering time is 8~10 min; when the vacuum deposition system adopts a pulsed laser deposition system, the system vacuum degree is 10 -3 ~10 -4 Pa, Ar flow rate is 40~80 sccm, O2 flow rate is 20~50 sccm, the incident laser energy is adjusted to 200~300 mJ, the frequency is 5~6 Hz, and the deposition time is 6~8 min; finally, the thickness of the obtained Al2O3 encapsulation layer is 10~20 nm.

10. The method for preparing the sandwich structure metal-semiconductor-metal MSM photoelectric detector with avalanche effect according to claim 8, characterized in that: In alloy targets, the weight ratio of doped metals is 1:4~1:5; in mosaic targets, the area ratio of doped metals is 1:8~1:4.

Citation Information

Cited By

  • Solar blind detector used in extreme temperature environment and preparation method thereof

    CN121793457A